URGENSI RATIFIKASI KONVENSI INTERNATIONAL LABOUR ORGANIZATION (ILO) NOMOR 189 TAHUN 2011 TENTANG PEKERJAAN YANG LAYAK BAGI PEKERJA RUMAH TANGGA TERHADAP TENAGA KERJA MIGRAN ASAL INDONESIA DI LUAR NEGERI - Muhammad Dandy; Evi Deliana; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Until moment this profession as assistant house ladder still seen adjacenteye Like in script ILO Convention No. 189 of 2011 concerning Decent Work ForWorker House Stairs, that profession house ladder still Keep going belittled,which historical no lucky, by because that very susceptible to discrimination inThing condition work and work , against abuse right basic and others. In scriptconvention this, explained that worker house ladder contribute big to globaleconomy, including increase opportunity work paid for man and woman withresponsibilities, family, and more coverage large for serve senior citizens ,children and people with limitations , and large income transfers within the andbetween countries. Convention this formed also because consideration, that in thecountry develop , opportunity work in the formal sector historical rare, bybecause that worker house ladder contribute on significant proportion in forcework national, which arrived moment this still marginalized . Study this is studylaw normative that is use studies literature in collection the data. Study thischaracter descriptive try to describe how the urgency implementation ratificationILO Convention No. 189 of 2011. Furthermore , research this use meaningfulqualitative data analysis explain and conclude the data that has been collected byauthor . Results from study this is explain protection to worker Indonesianmigrants based on ILO Convention No. 189 of 2011 concerning Decent Work ForWorker House Ladder as well as need the ratification of the ILO conventionnumber 189 of 2011 concerning decent work for domestic workers for Indonesianmigrant workers abroad, so that in the future no return repeated torture andbullying to workers Indonesian migrants .Keywords : Urgency -Ratification-Workers-Convention Indonesian Migrants